Evaluation of Emerging Threats of Contaminants in Boreholes along Ikot Effanga Dumpsite, Calabar Municipality, Nigeria - Ivon Ettah Akpang; Joseph Akaninyene Paul; Andem Andem Bassey; Otong Bassey Esio; Ebari Sylvanus Ekpe (Archives of Current Research International, 2017)
Aim: The study was aimed at evaluating the emerging threats of contaminants in boreholes along Ikot Effanga dumpsite. Methodology: Groundwater samples were aseptically collected from Five (5) boreholes around the dumpsite into a 1 liter bottle and leachates were also collected in two points of the dump site. Samples were collected monthly from April to June, 2016. The water and leachates were analyzed for heavy metals spectrophotometrically in mg/l. Physico-chemical parameters were also analyzed using appropriate methods. Results: The levels of turbidity, conductivity, dissolved oxygen, nitrate, manganese, iron, sulphate, chlorine, lead, phosphate and sodium of the leachates from the dump site were all above the WHO acceptable limit, but temperature, pH and total hardness were within the limit. The DO, pH, iron, lead, nitrate and phosphate content of ground water 2, 3, 4, 5 were all not within the WHO acceptable range. The levels of manganese were above the WHO limit for ground water 2, 4 and 5. Also, temperature, conductivity, total hardness, alkalinity, turbidity, sodium, chloride and sulphate content of the five (5) ground water samples were all within the WHO limit, but in most cases the control ground water (GW 1) recorded the lowest values. This denotes that the contaminated leachates from the dump site led to the corresponding contamination of the nearby ground waters, making them unsafe for consumption. Statistically, the temperature, conductivity, total hardness, alkalinity, NO3-, PO4-, turbidity, SO42-, Cl-, Mn, Fe, Pb and Na varied significantly between the ground waters at P<.05. Conclusion: The dumpsite led to the contamination of ground water, as a result, further research on the quality of the ground water need to be carried-out, in order to reveal the health consequences of drinking from ground water close to Ikot Effanga dump sites by evaluating the bacterial and coliform levels of these ground waters.